2021
DOI: 10.1021/acsami.1c02424
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the Voltage Decay Based on a Distinct Stacking Sequence of Oxygen Atoms for Li-Rich Cathode Materials

Abstract: Li-rich cathode materials possess a much higher theoretical energy density than all intercalated cathode materials currently reported and thus are considered as the most promising candidate for next-generation high-energy density Li-ion batteries. However, the rapid voltage decay and the irreversible phase transition of O3-type Li-rich cathode materials often lessen their actual energy density and limit their practical applications, and thus, effectively suppressing the voltage decay of Li-rich cathodes become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Mn 7+ was then reduced and returned to the original octahedral sites and there were also Mn 7+ ions in tetrahedral sites at the end of charging. Kleiner et al [95] quantified the migration track of TMs via synchrotron radiation XRD differential Fourier fitting. It was found that ~8% TMs occupied the tetrahedral sites in the Li layer during charging and ~2%-5% TMs occupied Li octahedral sites without the occupation of tetrahedral sites after discharge.…”
Section: Element Migrationmentioning
confidence: 99%
See 4 more Smart Citations
“…Mn 7+ was then reduced and returned to the original octahedral sites and there were also Mn 7+ ions in tetrahedral sites at the end of charging. Kleiner et al [95] quantified the migration track of TMs via synchrotron radiation XRD differential Fourier fitting. It was found that ~8% TMs occupied the tetrahedral sites in the Li layer during charging and ~2%-5% TMs occupied Li octahedral sites without the occupation of tetrahedral sites after discharge.…”
Section: Element Migrationmentioning
confidence: 99%
“…The O2type cathode material [96,97] then emerges and the special oxygen stack (ABCBA) enables TM ions to undergo , followed by the spontaneous formation of peroxide or trapped oxygen molecules accompanied by the reduction of Mn [94] . (B) TM migration in an LRMO from the octahedral TM sites via tetrahedral sites into octahedral Li sites [95] . (C) Comparison of crystal structures.…”
Section: Element Migrationmentioning
confidence: 99%
See 3 more Smart Citations